2016
DOI: 10.2519/jospt.2016.5774
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Bracing Increases Ground Reaction Forces and Reduces Knee and Hip Flexion During Landing

Abstract: Abdominal bracing reduces impact attenuation during landing. These altered biomechanics may have implications for lower-limb and spinal injury risk during dynamic tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
2
8
0
1
Order By: Relevance
“…However, the opposite effect was seen for thorax movement, with more movement during abdominal bracing lifts compared to without, in particular during the loaded lowering phase. These findings are in line with earlier findings showing that abdominal bracing increases lower limb stiffness during a drop landing (Campbell et al, 2016) and lumbar spine stiffness during a spinal perturbation trial . From this it can be concluded that any potential benefits of abdominal bracing including reductions of end-range strain and the impact of unwanted spinal perturbations (McGill, 1998;McGill and Karpowicz, 2009) may come at the cost of increased flexion of the thorax.…”
Section: Discussionsupporting
confidence: 94%
“…However, the opposite effect was seen for thorax movement, with more movement during abdominal bracing lifts compared to without, in particular during the loaded lowering phase. These findings are in line with earlier findings showing that abdominal bracing increases lower limb stiffness during a drop landing (Campbell et al, 2016) and lumbar spine stiffness during a spinal perturbation trial . From this it can be concluded that any potential benefits of abdominal bracing including reductions of end-range strain and the impact of unwanted spinal perturbations (McGill, 1998;McGill and Karpowicz, 2009) may come at the cost of increased flexion of the thorax.…”
Section: Discussionsupporting
confidence: 94%
“…In addition to these factors, psychosocial aspects may also be associated [35,36], including social relationships, self-esteem, mood, social roles, satisfaction with life and independence. Moreover, activation of abdominal bracing may limit movements and increase mechanical stress, providing greater energy expenditure [13,37]. In patients with chronic low back pain, the transverse abdominal muscle seems not to exhibit delayed activation [12], and multifidus activity may be changed, independent of abdominal bracing activation [13].…”
Section: Discussionmentioning
confidence: 99%
“…The ECA condition was defined as at least 20% of the normalized percentage of maximum voluntary isometric contraction (%MVIC) of the contralateral and ipsilateral internal obliques (CIO & IIO) of the dominant leg (the side used to kick a ball). A target of 20% of MVIC of the IO was adopted in this study based on the level of abdominal core activation which could offer optimal spinal stability as suggested in previous research [9, 10]. The dependent variables were the activity of gluteus medius (GMed), upper part of gluteus maximus (UGMax), lower part of gluteus maximus (LGMax) and biceps femoris (BF) of the dominant leg measured by the surface electromyography (EMG).…”
Section: Methodsmentioning
confidence: 99%
“…For monitoring of the muscle activity of the transverse abdominal wall, EMG activity of the transverse fibres of the internal obliques and the underlying transverse abdominis, which was named as IO in this study, was measured using the surface EMG methods [9, 13, 14]. Before placing EMG electrodes, skin preparation including hair removal, light abrasion with sandpaper and cleaning with isopropyl alcohol was completed to lower the skin impedance to <10 Ω (Ω).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation